Catalytic isoforms Tpk1 and Tpk2 of Candida albicans PKA have non-redundant roles in stress response and glycogen storage - Giacometti, Romina (2009)
Candida albicans cAMP-dependent protein kinase (PKA) is coded by two catalytic subunits (TPK1 and TPK2) and one regulatory subunit (BCY1). In this organism the cAMP/PKA signalling pathway mediates basic cellular processes, such as the yeast-to-hyphae transition and cell cycle regulation. In the present study, we investigated the role of C. albicans PKA in response to saline, heat and oxidative stresses as well as in glycogen storage. To fine-tune the analysis, we performed the studies on several C. albicans PKA mutants having heterozygous or homozygous deletions of TPK1 and/or TPK2 in a different BCY1 genetic background.We observed that tpk1 Δ/tpk1 Δ strains developed a lower tolerance to saline exposure, heat shock and oxidative stress, while wild-type and tpk2 Δ/tpk2 Δ mutants were resistant to these stresses, indicating that both isoforms play different roles in the stress response pathway. We also found that regardless of the TPK background, heterozygous and homozygous BCY1 mutants were highly sensitive to heat treatment. Surprisingly, we observed that those strains devoid of one or both TPK1 alleles were defective in glycogen storage, while strains lacking Tpk2 accumulated higher levels of the polysaccharide, indicating that Tpk1 and Tpk2 have opposite roles in carbohydrate metabolism. Copyright © 2009 John Wiley & Sons, Ltd.